2019
DOI: 10.1103/physrevresearch.1.033067
|View full text |Cite
|
Sign up to set email alerts
|

Power-law entanglement growth from typical product states

Abstract: Generic quantum many-body systems typically show a linear growth of the entanglement entropy after a quench from a product state. While entanglement is a property of the wave function, it is generated by the unitary time evolution operator and is therefore reflected in its increasing complexity as quantified by the operator entanglement entropy.Using numerical simulations of a static and a periodically driven quantum spin chain, we show that there is a robust correspondence between the entanglement entropy gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…The existence of l-bits predicts the absence of particle transport and thermalization in the MBL phase, but also an unbounded logarithmic growth of the bipartite entanglement entropy [9,19,[21][22][23][24][25] up to a nonthermal, extensive, saturation value. This behavior is in stark contrast with the thermal phase, where the entanglement entropy grows as a power law in time [26,27]. Without disorder, a linear growth of the entanglement entropy is typically observed [28].…”
mentioning
confidence: 88%
“…The existence of l-bits predicts the absence of particle transport and thermalization in the MBL phase, but also an unbounded logarithmic growth of the bipartite entanglement entropy [9,19,[21][22][23][24][25] up to a nonthermal, extensive, saturation value. This behavior is in stark contrast with the thermal phase, where the entanglement entropy grows as a power law in time [26,27]. Without disorder, a linear growth of the entanglement entropy is typically observed [28].…”
mentioning
confidence: 88%
“…A number of numerical studies demonstrated later, that for one-dimensional systems with bounded energy density, transport in the delocalized phase is subdiffusive, and thus conductivity in the thermodynamic limit vanishes through the entire phase diagram [10][11][12][13][14]. In addition to the anomalous transport, the delocalized phase shows sublinear growth of entanglement entropy [13,15,16], suppressed spreading of entanglement [17][18][19], intermediate statistics of eigenvalue spacing [20] and satisfies only a modified version of the eigenstates thermalization hypothesis (ETH) [21] (see [22] for a detailed review of the properties of the delocalized phase). A phenomenological explanation of the anomalous dynamical properties of the delocalized phase, based on rare blocking regions, was provided in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The problem can be mapped to a weakly interacting Majorana fermion model coupled to a static Z 2 gauge field [20][21][22][23][24][25][26][27][28][29], which for the considered dynamics becomes effectively disordered. In the noninteracting limit, we find that the gauge flux disorder localizes most of the Majorana fermions but fails to freeze the metallic and critical modes, leading to the observed subdiffusive dynamics although the system is overall nonergodic [30][31][32][33][34]. We identify the subdiffusive dynamics both in an algebraic spread of quantum correlations and the power-law growth of entanglement.…”
mentioning
confidence: 84%